How community participation in water and sanitation interventions impacts human health, WASH infrastructure and service longevity in low-income and middle-income countries: a realist review - Joel Negin; Seye Abimbola; Aaron Jenkins; Sarah Nelson; Dorothy Drabarek (BMJ Open)
Objective To understand how, and under what circumstances community participation in water and sanitation interventions impacts the availability of safe water and sanitation, a change in health status or behaviour and the longevity of water, sanitation and hygiene (WASH) resources and services.Design Realist review.Data sources PubMed, Web of Science and Scopus databases were used to identify papers from low-income and middle-income countries from 2010 to 2020.Eligibility criteria for selecting studies Criteria were developed for papers to be included. The contribution of each paper was assessed based on its relevance and rigour (eg, can it contribute to context, mechanism or outcome, and is the method used to generate that information credible).Analysis Inductive and deductive coding was used to generate context–mechanism–outcome configurations.Results 73 studies conducted in 29 countries were included. We identified five mechanisms that explained the availability, change and longevity outcomes: (1) accountability (policies and procedures to hold communities responsible for their actions and outcomes of an intervention), (2) diffusion (spread of an idea or behaviour by innovators over time through communication among members of a community), (3) market (the interplay between demand and supply of a WASH service or resource), (4) ownership (a sense of possession and control of the WASH service or resource) and (5) shame (a feeling of disgust in one’s behaviour or actions). Contextual elements identified included community leadership and communication, technical skills and knowledge, resource access and dependency, committee activity such as the rules and management plans, location and the level of community participation.Conclusions The findings highlight five key mechanisms impacted by 19 contextual factors that explain the outcomes of community water and sanitation interventions. Policymakers, programme implementers and institutions should consider community dynamics, location, resources, committee activity and practices and nature of community participation, before introducing community water and sanitation interventions.